Redox regulation at the site of primary growth: auxin, cytokinin and ROS crosstalk - Tognetti, Vanesa B; Bielach, Agnieszka; Hrtyan, Mónika (Plant, cell & environment, 2017)
To maintain the activity of meristems is an absolute requirement for plant growth and development, and the role of the plant hormones auxin and cytokinin in apical meristem function is well established. Only little attention has been given, however, to the function of the reactive oxygen species (ROS) gradient along meristematic tissues and its interplay with hormonal regulatory networks. The interdependency between auxin-related, cytokinin-related and ROS-related circuits controls primary growth and development while modulating plant morphology in response to detrimental environmental factors. Because ROS interaction with redox-active compounds significantly affects the cellular redox gradient, the latter constitutes an interface for crosstalk between hormone and ROS signalling pathways. This review focuses on the mechanisms underlying ROS-dependent interactions with redox and hormonal components in shoot and root apical meristems which are crucial for meristems maintenance when plants are exposed to environmental hardships. We also emphasize the importance of cell type and the subcellular compartmentalization of ROS and redox networks to obtain a holistic understanding of how apical meristems adapt to stress.
Keywords: Cytokinins; cytokininy; Reactive Oxygen Species; Indoleacetic Acids; plasticity; oxidace-redukce; vývoj rostlin; stress adaptation; Plant Development; apical meristem; Homeostasis; homeostáza; Oxidation-Reduction; kyseliny indoloctové; reaktivní formy kyslíku